REMEDIASI MISKONSEPSI PESERTA DIDIK SMP MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA MATERI PERPINDAHAN KALOR - Fardilah, Ahmad; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to determine the effectiveness of misconception remediation of the seventh grade students of Pontiank state middle school by using Problem Based Learning model for decrease the number of students misconception on the heat transfer lesson material. One group pretest-posttest was used as the design model in this research. The intact group technique was used as the technique of sampling. The sample were class VII D with 36 students. The data gained in the form of pretest and posttest would be analyzed in percentage calculate of reduction in the number of student misconception. Based on the data analysis, the average percentage of reduction misconception was 39.45%. The results of Mc Nemar significance test on dk = 1 and Î±= 5% showed > , were equal to 22,88 > 3,84. There was a conceptual change on the students significantly. The Decreasing Quantity Students that Misconception (DQM) Problem Based Learning model in remediating misconception were 39,44% (high category). The results of this research were expected to be used as the development material of PBL in remediation learning about the heat transfer material.Â Keywords: Heat Transfer, Misconception, Problem Based Learning, RemediationÂ